Analisis Kinerja Saham Pada Pt Astra Agro Lestari Tbk - Artie Arditha Rachman (Jurnal Ilmiah ESAI, 2007)
There are many indicators in measuring a company’s performance. The two of them are the fundamental analysis and the technical analysis. By using these analyses, this research evaluated the performance of PT Astra Agro Lestari Tbk, as a go public agricultural company listed in Jakarta Stock Exchange. The period used in this case was in 2006. The result showed that this company has a great performance. In the fundamental analysis, its condition of a good finance was shown through the best ratio in debt to equity ratio, return on asset, net profit margin, and operating profit margin. The return on equity was also in a great ratio although it’s still under other company’s ratio. In the other hand, using the technical analysis, its stock’s price fluctuated in a great movement following the composite index, which showed that the company had a positive respond to the market. Meanwhile, its rate of return and risk were in a prospective position. Its rate of return was the highest return in its sub sector and its rate of risk was the lowest one. Based on the result from this research, investors should not hesitate in having investment in PT Astra Agro Lestari Tbk., because this company is prospective enough as one of the stock investment choices. Kata Kunci: pengembalian, risiko, saham